The Effect of Macroeconomic Factors on the Stock Price Index of Developing Countries and Developed Countries in Asia 2001-2020 - Eliezer Yudha Nattan; Wisnu Mawardi (Budapest International Research and Critics University, 2021)
This study aims to determine whether macroeconomic factors influence stock price indexes in developed countries and developing countries in the Asian region during 2001-2020. Macroeconomic factors are world oil prices, world gold prices, interest rates, exchange rates against the USD, and gross domestic product (GDP). The countries that are the object of research are Indonesia, Japan, China, Hong Kong, and India. This research uses the panel data regression method. Based on the model estimation test, oil prices, gold prices, exchange rates, and GDP positively and significantly affect stock price indices in both developed and developing countries. On the other hand. The interest rate has a negative and significant influence on the stock price index of developing and developed countries.